Determinants of Female Teachers Progress to Leadership in Government Aided Primary Schools in Ntungamo District, Uganda - Mugizi, Wilson; Masheija, Paulus January (Open Journal of Leadership, 2019)
This study explored the determinants of female teachers’ progress to leadership in government-aided primary schools in Ntungamo District. Specifically, the study explored how personality characteristics, school factors and social factors determined female teachers’ progress to leadership in government- aided primary schools. This cross-sectional study used a sample of 210 respondents and data were collected using a questionnaire survey. Data were analysed using descriptive analysis that included frequencies, percentages and means, and inferential analyses that were correlation and regression. Descriptive results revealed that the level of female teachers’ progress to leadership was good, had strong personality characteristics and experienced favourable school and social factors. Regression results revealed that organisational factors and social were positive significant determinants of female teachers’ progress to leadership while personality characteristics were negative and insignificant determinants. Therefore, the conclusions reached were that personality characteristics were not the most probable factors that determined female progress to leadership in primary schools, school factors were essential for female teachers’ progress to leadership in primary schools, and social factors were imperative for female teachers’ progress to leadership in primary schools. It was thus recommended that bodies charged with promoting of female teachers such District Education Service Commissions and schools leadership should assess personality characteristics of women when promoting them to leadership, those charged with management of schools such as District Education Officers, Inspectors of Schools, Schools Management Committees and head teachers should ensure that school factors promote female teachers progress to leadership, and leadership of schools from national to local level and community members should ensure that social factors in place promote female teachers progress to leadership.
Keywords: Organizational Factors; Personality Characteristics; Progress to Leadership; Social Factors